Tasawuf Dan Perempuan Pemikiran Sufi-Feminisme Kh. Husein Muhammad - Najib, Muhammad Ainun (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract Husein Muhammad is often classified as a liberal feminist because of his involvement in the thoughts and movements of feminism in Indonesia. Some researchers emphatically liberal feminism in the thinking of Kiai Husein. However, if it is read carefully, there are slips of feminist thought and movement of Kiai Husein with a Sufistic nuance even though it starts from the interpretation of gender or fiqh of the female which is indeed the core of his science. Kiai Husein's Sufistic thought traces are clearly seen in three ways. First, women are sacred and respectable creatures. This is excerpted from the speech of the Muhammad in the event of hajj WADA'. Second, loving equality is a loving God (mahabbah). For Kiai Husein, the sign of someone loving his Lord is a sincere recognition of the equality of men and women. The use of the concept of mahabbah in feminism confirms, in the thought of Kiai Husein, Sufism in feminism. Third, women are not a matter of the body, but spirit. In the midst of the ideology of capitalism which makes the female body a vessel of sensuality, Kiai Husein defended women through human essence, including men, which lies in the spirit. Keywords: Woman, Sufism, KH. Husein Muhammad, thoughts, feminism. Abstrak Husein Muhammad acapkali diklasifikasikan sebagai feminis liberal lantaran keterlibatannya dalam pemikiran dan gerakan feminisme di Indonesia. Beberapa peneliti dengan tegas feminisme liberal dalam pemikiran Kiai Husein. Namun, bila dibaca dengan saksama, terselip pemikiran dan gerakan feminisme Kiai Husein yang bernuansa sufistik sekalipun hal itu berawal dari tafsir gender atau fikih perempuan yang memang menjadi core keilmuannya. Jejak pemikiran sufistik Kiai Husein terlihat dengan gamblang dalam tiga hal. Pertama, Perempuan adalah makhluk suci dan terhormat. Ini disarikan dari pidato Nabi Muhammad dalam peristiwa haji wada’. Kedua, mencintai kesetaraan adalah mencintai Tuhan (mahabbah). Bagi Kiai Husein, tanda seorang mencintai Tuhannya adalah pengakuan yang tulus terhadap kesetaraan laki-laki dan perempuan. Penggunaan konsep mahabbah dalam feminisme menegaskan, dalam pemikiran Kiai Husein, tasawuf dalam feminisme. Ketiga, perempuan bukan soal tubuh, tapir ruh. Di tengah ideologi kapitalisme yang menjadikan tubuh perempuan sebagai bejana sensualitas, Kiai Husein melakukan pembelaan terhadap perempuan melalui esensi manusia, termasuk laki-laki, yang terletak pada ruh. Kata Kunci: Perempuan, tasawuf, KH. Husein Muhammad, pemikiran.